TINJAUAN YURIDIS PUTUSAN PENGADILAN NEGERI CIBADAK NOMOR 12/Pdt.G/2021/PN Cbd Jo. PASAL 19 UU POKOK AGRARIA - Shite, Magdalena Megawati (Truth de Journal, 2025)
The issuance of Certificate of Title No. 7778/1975 by the National Land Agency of Sukabumi Regency was sued at the Cibadak District Court because it was considered a juridical defect in the recognition of ownership, which gave rise to a legal permit. This study aims to analyze the evidentiary strength between the Authentic Deed and the Deed Under the Hand, as well as the judge's consideration in the decision of the Cibadak District Court Number 12/Pdt.G/202/PN Cbd regarding witness statements. The research method used is qualitative research with a normative juridical approach, relying on primary and secondary data sources, as well as data collection techniques through observation and interviews. The study's results show that the Certificate of Property Rights is a genuine document with strong legal force and cannot be contested. However, the facts on the ground show that there is a legal loophole that results in the opening of the law for certificate holders. Land certificates, although a strong proof of ownership, do not fully guarantee legal certainty and protection, so they require more attention in their application.